BIOKIMIAWI RIZOSFER BIBIT ROTAN PADA PEMUPUKAN NITROGEN DARI SUMBER BERBEDA - Lisa Indriani; Muhammad Basir Chio; Aiyen Tjoa; Andri Tanra Tellu (Jurnal Agrotech, 2020)
Root and soil interactions will alter the biochemical status of the rhizosphere, the acquisition of nutrients and impacted to plant growth. The biochemical of the rhizosphere is strongly influenced by the agriculture input e.g. fertilizer, herbicides and farm management system. Application of fertilizers, their effects are robust and difficult tobe quantified. The effect of fertilizer on the biochemical status rhizosphere and plant growth is different depending on the type of fertilizers, growth media, plant species, and also the environment condition, while the effect on plants will be specific to each plant. This research investigated on the effect of N inorganic fertilizer inputs from two sources namely Urea (CO(NH2)2) and Ammonium Sulfate or ZA ((NH4)2.SO4), and different fertilization method (homogenous and localized). Experiments showed application of N-Urea and N-ZA fertilizers reduced the rhizosphere pH until 1,4 point. However, acidity of the rhizosphere reduced microorganism colonies and respiration rate.